Antianemic Treatment of Cancer Patients in German Routine Practice: Data from a Prospective Cohort Study—The Tumor Anemia Registry. (4th February 2016) - Steinmetz, Tilman; Schröder, Jan; Plath, Margarete; Link, Hartmut; Vogt, Michèle; Frank, Melanie; Marschner, Norbert
Abstract : The aim of this prospective cohort study was to assess current antianemic treatment of cancer patients in German routine practice, including diagnostics, treatments, and quality of life (QoL). 88 study sites recruited 1018 patients at the start of antianemic treatment with hemoglobin (Hb) levels <11 g/dL (females) or <12 g/dL (males). Patients were followed up for 12 weeks. 63% of the patients had inoperable solid tumors, 22% operable solid tumors, and 15% hematological malignancies. Over 85% received chemotherapy. Median age was 67 years; 48% were male. Red blood cell transfusions (RBCTx) were given to 59% of all patients and to 55% of the patients with Hb ≥8 g/dL on day 1 of the observation period (day 1 treatment). Erythropoiesis-stimulating agents (ESAs) were the second most frequently applied day 1 treatment (20%), followed by intravenous (IV) iron (15%) and ESA + IV iron (6%). Only about a third of patients were tested for blood serum iron parameters at the start of treatment. Overall, more than half of the patients had long-term responses to antianemic therapy. Our data suggest that in routine practice diagnostics for treatable causes of anemia are underused. A high proportion of cancer patients receive RBCTx. It should be discussed whether thorough diagnostics and earlier intervention could decrease the need for RBCTx. This trial is registered withNCT01795690 .